2009
DOI: 10.1123/jsep.31.4.444
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perceptions of Child-to-Parent Socialization in Organized Youth Sport

Abstract: The purpose of this study was to enhance understanding of how parents are socialized by their children's organized youth sport participation. Five semistructured focus groups were conducted with youth sport parents (N = 26) and analyzed using qualitative methods based on Strauss and Corbin (1998). Sixty-three underlying themes reflected parents' perceived socialization experiences resulting from their children's organized youth sport participation. Each theme represented 1 of 11 subcategories of parental chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
136
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 29 publications
7
136
0
1
Order By: Relevance
“…Parents' recognition and 668 understanding of their child's needs and their capacity to adapt to meet these has previously 669 been reported (e.g. Dorsch et al, 2009;, but is often overshadowed within wider 670 discussions focusing on the determinants of parents' behaviours and/or associated child 671 effects. For example, parents' empathy with their child has been framed as a contributory 672 factor to parents' emotional reactions at competitions, and therefore, as a potential area for 673 development (Holt et al, 2008;Knight & Holt, 2013).…”
mentioning
confidence: 99%
“…Parents' recognition and 668 understanding of their child's needs and their capacity to adapt to meet these has previously 669 been reported (e.g. Dorsch et al, 2009;, but is often overshadowed within wider 670 discussions focusing on the determinants of parents' behaviours and/or associated child 671 effects. For example, parents' empathy with their child has been framed as a contributory 672 factor to parents' emotional reactions at competitions, and therefore, as a potential area for 673 development (Holt et al, 2008;Knight & Holt, 2013).…”
mentioning
confidence: 99%
“…Therefore, it was beneficial to obtain a qualitative comprehensive account about this subject from athletes (Dorsch, Smith, & McDonough, 2009). A qualitative, case study method was employed to obtain these accounts and help to uncover information about parental involvement and overinvolvement (Hancock & Algozzine, 2011;Stake, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…First, Grolnick and colleagues (2002) found that as parents become more ego-involved in their child's activities, they naturally find supporting children's perceptions of autonomy and relatedness more challenging (Grolnick, Gurland, DeCourcey, & Jacob, 2002). This finding has been supported in sport where researchers have reported more intense parent emotions as involvement in children's sport increases (e.g., Clarke & Harwood, 2014;Dorsch et al, 2009). Also, susceptibility to sport-parenting challenges is linked to a parent's own learning history in performance domains .…”
Section: Barriers To Parental Support Of Children's Basic Psychologicmentioning
confidence: 99%
“…This research has consistently found sport-parenting to be a highly emotional experience, with parents describing a range of emotions including disappointment, worry, embarrassment, anger, and helplessness (e.g., Dorsch, Smith, & McDonough, 2009;Harwood & Knight, 2009a;2009b;Knight & Holt, 2013a). When Wiersma and Fifer (2008) explored 55 youth sport parents' experiences, the authors identified four key categories of parent experience: a) joys, b) challenges, c) factors that explain parent behaviour, and d) adult responsibility.…”
Section: Parent Perspectives Of Sport Involvementmentioning
confidence: 99%
See 1 more Smart Citation